2010
DOI: 10.1111/j.1523-1739.2010.01567.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Citizen Science Programs to Identify Host Resistance in Pest-Invaded Forests

Abstract: Threats to native forests from non-native insects and pathogens (pests) are generally addressed with methods such as quarantine, eradication, biological control, and development of resistant stock through hybridization and breeding. In conjunction with such efforts, it may be useful to have citizen scientists locate rare surviving trees that may be naturally pest resistant or tolerant. The degree of resistance of individual trees identified in this way can be tested under controlled conditions, and the most re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 32 publications
1
48
0
Order By: Relevance
“…Once the cuttings were established, both control and resistant cuttings were inoculated with HWA and adelgid settlement and survival was assessed. Adult HWA densities were significantly lower on the resistant cuttings than on the susceptible cuttings (Ingwell and Preisser 2011), supporting the hypothesis that some rare eastern hemlock individuals possess a degree of HWA resistance, and implying that this resistance is manifest as antibiosis.…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…Once the cuttings were established, both control and resistant cuttings were inoculated with HWA and adelgid settlement and survival was assessed. Adult HWA densities were significantly lower on the resistant cuttings than on the susceptible cuttings (Ingwell and Preisser 2011), supporting the hypothesis that some rare eastern hemlock individuals possess a degree of HWA resistance, and implying that this resistance is manifest as antibiosis.…”
Section: Introductionsupporting
confidence: 66%
“…Previous research (Ingwell and Preisser 2011) identified eight putatively HWA-resistant eastern hemlocks growing on state-owned land adjacent to the Delaware Water Gap National Recreation Area in northern New Jersey, of which trees #1-5 have been tested for resistance by bioassay of clonal saplings (Ingwell and Preisser 2011). Trees #1-5 were sampled at all collection dates, and trees #6 and #7…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations